Republic of Indonesia Financial Sector Assessment Program : CPSS-IOSCO Recommendations for Securities Settlement Systems--The Equity and Corporate Bonds Securities Settlement Systems - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
This assessment forms part of the joint International Monetary Fund (IMF) World Bank Indonesia Financial Sector Assessment Program (FSAP) which is being undertaken during 2009-2010. The assessment, which covers the private sector equity and corporate bonds securities system's observance of the Committee on Payment and Settlement Systems / International Organization of Securities Commissions (CPSS/IOSCO) recommendations for securities settlement systems, was conducted during an ad hoc mission. The assessment focuses on two types of trades. First the clearing and settlement process is assessed as regards equity transactions traded on the stock exchange Indonesian Stock Exchange (IDX), cleared through the Clearing and Guarantee Corporation (KPEI) clearing system (e-CLEARS) and settled through the Central Securities Depository for the Stock Exchange securities (KSEI) settlement system (C-BEST). In addition, the assessment focuses on corporate bond transactions, which are traded outside the exchange and settled through the KSEI settlement system (C-BEST).